La diplomazia culturale americana, la Guerra fredda e il cinema di Hong Kong negli anni Cinquanta = American cultural diplomacy, Cold War, and Hong Kong cinema in the 1950s - Lee, Sangjoon (2022)
Drawing on archival materials from The Asia Foundation (Taf) Records at the Hoover Institution Archives, the University of Hong Kong's manuscripts and special collections, and the San Francisco International Film Festival Papers, this article is a focused account of the early history of Taf and its motion picture projects in Cold War Hong Kong. The study will reveal the unknown story of Chang Kuo-sin's anti-Communist motion picture studio in Hong Kong. The Asia Pictures, and the film Nobody's Child that was screened at the San Francisco International Film Festival, with Taf's support.